The effect of vitamin D deficiency on glycemic control in patients with type 2 diabetes mellitus - Neveen Rashad Mostafa; Abeer Ahmed Mohamed Ali; Roy Rillera Marzo (PAGEPress Publications, 2023)
Multiple factors are involved in the development of type 2 diabetes mellitus (T2DM), but an imbalance between free radical formation and antioxidant removal is the main cause of diabetic complications. Micronutrients with antioxidant properties may have a role in the development of diabetes mellitus (DM) and its complications. Vitamin D has recently been found to have membrane antioxidant effect and a relationship to the development of T2DM, as it can modify its risk. Whether vitamin D deficiency has an effect on hyperglycemia in diabetic patients or not need further study. Our aim was to examine the effect of vitamin D deficiency on glycemic control in T2DM. We examined the vitamin D levels of 100 patients with T2DM and correlated them with fasting blood sugar and glycated hemoglobin A1c (HbA1c) levels. High levels of fasting blood sugar and HbA1c levels were significantly associated with vitamin D deficiency. Vitamin D deficiency negatively affects glycemic control in patients with T2DM.